A Probability Integral on η-fuzzy Measure - CHANG Xin-qi; ZHAO Hui; WU Yang (Journal of Harbin University of Science and Technology)
For the study of relevant definitions and theorems of fuzzy integrals, a fuzzy measure is first defined; then a pair of optimized Einstein operators of the form are designed, which are λ-fuzzy quasiproduct operator and λ-fuzzy quasisum operator respectively. It is proved that the T triangular norm and S triangular norm conditions are satisfied. Finally, the definition of λ-fuzzy product probability integral and its theorem are given on the η-fuzzy measure space, and the proof of the theorem is also given, thus enriching the content of fuzzy measure theory.